Studying 124-128Ba Transitional nuclei in the IBM Framework (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Many properties of nuclear structure for even-even  isotopes have been investigated with  and  .They examined carefully with benefit from continuously updating of nuclear decay schemes. Low-lying energy levels for even-even positive parity states, mixed symmetry states (MSS), reduced electric quadruple transitions probabilities , branching ratios, reduced magnetic dipole transitions probability ,  ratio, reduced electric monopole transitions probability  and mixing ratio  and potential energy surface  have been studied.   In the framework of  noted the competition between the two parameters (  and ) in 124-128Ba isotopes were the increases  of a0 associated with decreases of a2 which mean that the γ-unstable features were continuous increases with opposite of rotational properties , in IBM-2 χπ and χν were (-1.3 and  around 0.7) which signified similarity  with IBM-1 expected. 124-128Ba isotopes described to be transitional nuclei , transitional between SU(3) and O(6) features.